Modeling of digital converter for GSM signals with MATLAB - Metodi Traykov; Radoslav Mavrevski; Ivan Trenchev (Institute of Advanced Engineering and Science, 2019)
In this study will simulate steady state of Digital Down Convertor (DDC) for GSM signal with a narrow frequency range. The MATLAB model that is described in this article simulates the work of the TIGC4016 Quad Digital Down Converter. This converter is used for digital mixing (down conversion) of signals, narrow band low-pass filtering and decimation. To implementation of the model, we use high sample-rate (69,333 MSPS) bandpass signal. The result contains low sample-rate (270.83 KSPS) baseband signal, thus facilitating the demodulation process.